Preferred and non-preferred creditors - Tito Cordella; Andrew Powell (Inter-American Development Bank (IDB), 2021)
International financial institutions (IFIs) generally enjoy preferred creditors treatment (PCT). Although PCT rarely appears in legal contracts, when sovereigns restructure bilateral or commercial debts, they normally pay IFIs in full. This paper presents a model where a creditor, such as an IFI, that can commit to lend limited amounts at the risk-free rate and can refrain from lending into arrears is always repaid and adds value. The analysis suggests that IFIs and market lenders can both enhance welfare, even if banning commercial borrowing can sometimes be optimal. To maintain their status, preferred lenders should offer low cost financing in volumes that are consistent with countries' incentives to repay even in bad states. This suggests such lenders should not differentiate lending interest rates according to risk and should not participate in the restructuring of commercial debt.
Keywords: F34; H63; O19; P33; 330; Preferred Creditor Treatment; Preferred Creditor Status; Sovereign Debt; Sovereign Defaults; International Financially Institutions; Emergency Financing